The Spirit of Atonement: Pentecostal Contributions and Challenges to the Christian Traditions: oleh Steven M. Studebaker - Monte Lee Rice (Asosiasi Teolog Indonesia, 2021)
Sebuah resensi untuk buku The Spirit of Atonement: Pentecostal Contributions and Challenges to the Christian Traditions